Learn Muay Thai Basic Movement in Virtual Reality and Sattolo Shuffle Algorithm - Wongso, Martin; Istiono, Wirawan (International Journal of Science, Technology & Management, 2023)
Muay Thai is a martial art from Thailand that uses punches and various clinching movements. Muay Thai is one martial art whose popularity is growing and is in great demand, including in Indonesia. However, very few people still know the basics of this Muay Thai martial art. Therefore, a media that can introduce Muay Thai martial arts is needed. In this study, to introduce the basic movements of Muay Thai martial arts, Virtual Reality technology is used, which aims to make it easier for users to understand and practice basic Muay Thai movements correctly. In this study, the method used to design virtual reality games is the Sattolo Shuffle algorithm which functions to generate unique and different randomized Muay Thai movement animation results. To measure the level of user acceptance of learning Muay Thai using VR technology, the GUESS method is used. From the result of GUESS method, it was found the user acceptance rate is 83.84%, which means the user is "satisfied" with the application that has been made to learn basic Muay Thai. Based on this level of acceptance, it can be concluded, that the virtual reality game introducing Muay Thai using the sattolo shuffle algorithm can be used as an alternative tool to learn basic Muay Thai.